Image Compression-Encryption Scheme via Fiber Specklegram-Based Compressive Sensing and Double Random Phase Encoding - Yan Liu; Yaohua Hu; Yang Li; Qi Qin; Guangde Li; ZhongWei Tan; Muguang Wang; FengPing Yan (IEEE Photonics Journal, 2020)
An image compression-encryption scheme utilizing the combination of fiber specklegram-based compressive sensing (CS) and double random phase encoding (DRPE) was demonstrated. The original image is compressed and encrypted by CS and then re-encrypted by DRPE. The measurement matrices for CS are constructed from multimode fiber specklegrams resulting from modes excitation and interference, which show better performance compared with those based on Gaussian random variables. Since fiber specklegrams have strong dependence on configuration, such measurement matrix can be constructed either by one specklegram or by specklegrams from different launched wavelengths. The double-encrypted image demonstrated good safety and reliability in several common attacks and presented high key sensitivity, which indicates good performance of the proposed scheme.